Bagaimana Atribut Produk, Sertifikasi Halal, dan Sertifikasi Labdoor Mempengaruhi Keputusan Pembelian Suplemen Whey Protein? - Azca, Rafie Mumtaz; Hidayati, Nurul; Zahra, Nisa (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2025)
This research aimed to analyze customer characteristics, the influence of product attributes, halal certification, and labdoor certification on whey protein purchasing decisions among Muslim customers on the island of Java. The research was carried out from January to December, 2023. The sampling method was purposive sampling. The data analysis method for this research used descriptive analysis and SEM-PLS. The research revealed that the majority of customers were female students aged 17-23 with limited income. Product attributes and labdoor certification significantly impacted purchasing decisions, while halal certification, although positive, lacked statistical significance. The study suggested managerial implications for whey protein industry players, emphasizing strategies such as Porter's Five Forces analysis to enhance competition, buyer and supplier bargaining power, and counter threats from substitutes and new products.